Smoking among adolescents is associated with their own characteristics and with parental smoking: cross-sectional study - Andrade, Rafaela Campos Cuissi de; Ferreira, Aline Duarte; Ramos, Dionei; Ramos, Ercy Mara Cipulo; Scarabottolo, Catarina Covolo; Saraiva, Bruna Thamyres Ciccotti; Gobbo, Luis Alberto (São Paulo Medical Journal, 2017)
BACKGROUND: This study aimed to analyze the association between smoking during adolescence and the characteristics of smoking and alcohol consumption among their parents. DESIGN AND SETTING: Cross-sectional study in Londrina (PR), Brazil. METHODS: The subjects comprised 1,231 adolescents aged 14-17 years. The adolescents and their parents answered a self-report questionnaire that asked for sociodemographic information and data on smoking and alcohol consumption. Multiple logistic regression models were used to analyze associations between smoking among adolescents and their characteristics (age, sex, period of the day for attending school, alcohol consumption and socioeconomic level) and their parents’ characteristics (smoking, alcohol consumption, age and education level), adjusted according to the adolescents’ characteristics (sex, age and socioeconomic level). RESULTS: The prevalence of smoking among adolescents was 3.4% (95% confidence interval, CI: 2.4-4.4). Adolescents whose mothers or fathers were smokers were 2.0 and 2.5 times more likely to be smokers, respectively. The prevalence of smoking among adolescents with a smoking mother was 7.1% (95% CI: 2.6-10.7) and a smoking father, 5.4% (95% CI: 1.6-8.5). There were significant associations between smok- ing adolescents and age [5.2% (95% CI: 3.3-6.6)], studying at night [9.6% (95% CI: 4.0-15.5)] and alcohol consumption [69.0% (95% CI: 55.0-83.0)]. It was observed that the number of alcoholic beverage doses consumed was higher among smoking adolescents (P = 0.001). CONCLUSION: Adolescent smoking was associated with smoking by their parents, regardless of the gender of the parents or adolescents. Age, alcohol consumption and studying at night are characteristics of adolescents that can contribute towards smoking.